Ned Kelly as memory dispositif : media, time, power, and the development of Australian identities - Basu, Laura, 1981- (Media and cultural memory, 2013)
Nineteenth-century outlaw Ned Kelly is perhaps Australia's most famous historical figure. This book explains the processes by which the cultural memory of Kelly has developed over time, and how it has related to negotiations of group identity. It breaks new grounds in memory studies by showing how memories are formed and develop through tangles of relations - memory dispositifs - and by furthering understanding of the relationships between cultural memory and national identity, at a time when matters of identity are more urgent than ever.